Carbonate buffering and metabolic controls on carbon dioxide in rivers. Issue 4 (11th April 2017) - Stets, Edward G.; Butman, David; McDonald, Cory P.; Stackpoole, Sarah M.; DeGrandpre, Michael D.; Striegl, Robert G.
Abstract: Multiple processes support the significant efflux of carbon dioxide (CO2 ) from rivers and streams. Attribution of CO2 oversaturation will lead to better quantification of the freshwater carbon cycle and provide insights into the net cycling of nutrients and pollutants. CO2 production is closely related to O2 consumption because of the metabolic linkage of these gases. However, this relationship can be weakened due to dissolved inorganic carbon inputs from groundwater, carbonate buffering, calcification, and anaerobic metabolism. CO2 and O2 concentrations and other water quality parameters were analyzed in two data sets: a synoptic field study and nationwide water quality monitoring data. CO2 and O2 concentrations were strongly negatively correlated in both data sets ( ρ  = −0.67 and ρ  = −0.63, respectively), although the correlations were weaker in high‐alkalinity environments. In nearly all samples, the molar oversaturation of CO2 was a larger magnitude than molar O2 undersaturation. We used a dynamically coupled O2 CO2 model to show that lags in CO2 air‐water equilibration are a likely cause of this phenomenon. Lags in CO2 equilibration also impart landscape‐scale differences in the behavior of CO2 between high‐ and low‐alkalinity watersheds. Although the concept of carbonate buffering and how it creates lags in CO2 equilibration with the atmosphere is well understood, it has not been sufficiently integrated into our understanding of CO2 dynamics in freshwaters. We argue that the consideration of carbonate equilibria and its effects on CO2 dynamics are primary steps in understanding the sources and magnitude of CO2 oversaturation in rivers and streams. Key Points: Carbonate buffering is a major control on CO2 oversaturation in streams and rivers Continuous CO2 oversaturation can occur due to diel cycles of production and respiration, especially in high‐alkalinity waters Landscape‐scale patterns of CO2 and DIC are differentiated between high‐ and low‐alkalinity waters due to carbonate buffering Plain Language Summary: Carbon dioxide (CO2 ) emission from streams and rivers is known to be large. The source of CO2 in these systems is of high interest to researchers because it provides important clues about the carbon cycle and the overall biogeochemical functioning of freshwaters. The scientific questions surrounding CO2 emissions from freshwaters have focused on whether CO2 is produced within the aquatic environment through the decomposition of organic material or whether CO2 is produced mostly in soil and groundwater and then delivered to freshwater environments where it is passively emitted to the atmosphere. Both explanations have a basis in reality, and yet neither fully explains the magnitude of estimated CO2 emissions. We examined how CO2 interacts with the rest of the carbonate buffering system to structure CO2 emission to the atmosphere. We found that daily cycles in photosynthesis and decomposition can create continuous CO2 oversaturation because of lags created through carbonate buffering. At the landscape scale, differences were evident in CO2 excess between watersheds having high versus low carbonate buffering. Our conclusions highlight that carbonate buffering is the primary control on CO2 concentration in surface waters and needs to be considered to understand the observations of CO2 excess in freshwaters.